Vietnam Urban Wastewater Review - World Bank (Washington, DC, 2014)
Vietnam is facing the challenge of trying to keep pace with increasing environmental pollution associated with rapid urbanization, especially in the larger cities. Over the past 20 years, the Government of Vietnam has made considerable effort to develop urban sanitation policies, legislations and regulations, and to invest in urban sanitation including wastewater treatment systems. This study is one of three country studies conducted in the emerging countries of Vietnam, the Philippines, and Indonesia as part of the East Asian urban sanitation review. It reviews the effectiveness of the wastewater sector in Vietnam and makes recommendations to the Government on actions to scale up the sector to improve its performance. Lessons that emerge from this study can be considered for the on-going and or the next generation of wastewater systems.